2009
DOI: 10.1177/0170840609104803
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Rivalry of Competing Institutional Logics

Abstract: We investigated an organizational field where competing institutional logics existed for a lengthy period of time. We identified four mechanisms for managing the rivalry of competing logics that facilitated and strengthened the separate identities of key actors, thus providing a way for competing logics to co-exist and separately guide the behaviour of different actors. We contribute to the institutional literature by showing that competing logics can co-exist and rivalry between logics can be managed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,383
6
52

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,371 publications
(1,540 citation statements)
references
References 42 publications
30
1,383
6
52
Order By: Relevance
“…Firstly, we extend the current literature on institutional logics by providing an empirical illustration for multiple logic configurations in the sharing economy field, going beyond such approaches that focus on dualistic nature of conflicting logics across different institutional contexts that prevail in the extant literature (e.g. Reay and Hinings 2009;Pache and Santos 2010;Ocasio and Radoynovska 2016). We contribute to the institutional scholarship longstanding interest in the interaction between agentic use of logics as tools and the consequences of these uses on strategy practice.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Firstly, we extend the current literature on institutional logics by providing an empirical illustration for multiple logic configurations in the sharing economy field, going beyond such approaches that focus on dualistic nature of conflicting logics across different institutional contexts that prevail in the extant literature (e.g. Reay and Hinings 2009;Pache and Santos 2010;Ocasio and Radoynovska 2016). We contribute to the institutional scholarship longstanding interest in the interaction between agentic use of logics as tools and the consequences of these uses on strategy practice.…”
Section: Resultsmentioning
confidence: 94%
“…Dunn and Jones 2010;Jarzabkowski et al 2013;Reay and Hinings 2009;Schneiberg and Clemens 2006). Greenwood et al (2010) initially used the 'institutional complexities' term when articulating the incompatible demands of different stakeholders.…”
Section: Institutional Logics and Complexitiesmentioning
confidence: 99%
“…In addition, we note earlier that found that Pedro Almodovar maintained a symbiotic career with his brother Augustin, who over the years has been committed to managing the "dirty part of business" (184) in order to help Perdo's creativity flourish. Overall, these studies draw attention to the increased likelihood of multiple and often competing institutional logics existing in collaborative, innovative contexts (e.g., Reay & Hinings, 2009) which inevitably pose high demands for organizational leaders and ask for dual leadership solutions. analysis of Italian operas is rare and instructive because it focuses simultaneously on two coexisting configurations of leadership at two different levels of organizations.…”
Section: Creative Brokersmentioning
confidence: 99%
“…There is, however, mounting evidence that organizations are subject to competing institutional demands within their organizational fields (Reay and Hinings, 2009;Scherer et al, 2013), and that these conflicting demands influence IT innovation adoption (Butler, 2003) and diffusion (Currie and Guah, 2007). However, existing information systems research has primarily examined one category of conflictsmisalignments between the organizational field and the institutional demands embodied within the IT artefact (see Gosian, 2004;Jensen et al, 2009) (STREAM 2).…”
Section: Stage Of Adoption Type Of It Innovation (Authors) Intentionmentioning
confidence: 99%